Azerbaijan : Country Environmental Analysis - World Bank (Washington, DC, 2013)
The Country Environmental Analysis, presents a review of environmental priorities, public environmental expenditures and the supporting institutional framework and makes recommendations to improve the efficiency and effectiveness of public environmental expenditure in Azerbaijan. The focus is to identify areas for improvement and changes to ensure that the process of establishing environment-related priorities is sufficiently comprehensive. The report concludes that investment effectiveness is key to environmental improvements and without significant political backing, monitoring environmental progress will continue to be based on individual project records. Also, without a clear decision on monitoring, the State Environmental Program will fall short of its potential. The report makes specific recommendations to fulfill the objectives and address the challenges identified.